2022
DOI: 10.1057/s41599-022-01353-8
|View full text |Cite
|
Sign up to set email alerts
|

Community-scale big data reveals disparate impacts of the Texas winter storm of 2021 and its managed power outage

Abstract: Aggregated community-scale data could be harnessed to provide insights into the disparate impacts of managed power outages, burst pipes, and food inaccessibility during extreme weather events. During the winter storm that brought historically low temperatures, snow, and ice to the entire state of Texas in February 2021, Texas power-generating plant operators resorted to rolling blackouts to prevent collapse of the power grid when power demand overwhelmed supply. To reveal the disparate impact of managed power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The research will specifically focus on the inaccessibility of grocery stores through multiple access indicators while accounting for the specific disproportionate impact on socially vulnerable populations. While the extant literature recognizes importance of access to facilities for community resilience in disasters [29][30][31] , there is limited empirical and observational insights to inform about the impacts of disasters on access to grocery stores 5,32 . In order to address the knowledge gap of using empirical and observational data to capture accessibility, the research presents an innovate method which harnesses and analyses location-based data to examine the equitable access to grocery stores during different phases of the disaster.…”
mentioning
confidence: 99%
“…The research will specifically focus on the inaccessibility of grocery stores through multiple access indicators while accounting for the specific disproportionate impact on socially vulnerable populations. While the extant literature recognizes importance of access to facilities for community resilience in disasters [29][30][31] , there is limited empirical and observational insights to inform about the impacts of disasters on access to grocery stores 5,32 . In order to address the knowledge gap of using empirical and observational data to capture accessibility, the research presents an innovate method which harnesses and analyses location-based data to examine the equitable access to grocery stores during different phases of the disaster.…”
mentioning
confidence: 99%
“…This result is significant in two aspects: first, the results reveal one mechanism causing lower-income areas recover more slowly after flood events. A number of studies 33,34 have reported the slow recovery of low-income areas after flood events in Harris County. The result presents one mechanism that negatively affects such slow recovery due to hazardexposure homophily.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical significance of this finding can be viewed from two aspects: first, this finding reveals one possible mechanism that hinders low-income areas from coping and recovering from flood impacts. The literature 33,34,37 provides strong evidence about greater impacts and slower recovery of low-income areas during flood events and has attributed the greater impacts and slower recovery to socio-economic characteristics [38][39][40] . The finding in this study however, reveals that hazard-exposure homophily (or lack of heterophily) reduces the number of resourceful social links available to low-income areas, and thus could negatively affect their resilience and recovery.…”
Section: Groupmentioning
confidence: 99%
“…In addition to flood reports and social media activities, recent studies show that telemetry-based human activity fluctuations, which is registered by the concentration of aggregated usage of cellphone users in specific areas can signal flood inundation or other disaster-related impacts 82,83 . To incorporate information regarding human activity in our flood nowcasting model, we obtained digital traces of human activities for the study timeframe from Mapbox.…”
Section: Overview Of the Model Development And Evaluationmentioning
confidence: 99%